FAKTOR PENENTU PEMBAYARAN ZAKAT, INFAQ, SHODAQOH (ZIS) MELALUI FINTECH - Tuti Alawiyah; Nurhadi Kamaluddin (Monex: Journal of Accounting Research, 2022)
The industrial revolution 4.0 changes the form of activities that were previously carried out directly, which can be done indirectly throught digitally. ZIS payments made directly by muzakki can currently be made through fintech. ZIS payments through fintech are currently in great demand by muzakki. The purpose of the research is to know the factors that determine the payment of zakat through fintech. This research uses SmartPLS 3 in the statistical tests.The results of this research found that the use of fintech is only influenced by the quality of fintech but is not influenced by the quality of information. Fintech user satisfaction is influenced by the quality of fintech and the quality of information. The success of fintech is influenced by the satisfaction of using fintech and the use of fintech.